Saporin as a Commercial Reagent: Its Uses and Unexpected Impacts in the Biological Sciences—Tools from the Plant Kingdom - Leonardo R. Ancheta; Patrick A. Shramm; Raschel Bouajram; Denise Higgins; Douglas A. Lappi (Toxins, 2022)
Saporin is a ribosome-inactivating protein that can cause inhibition of protein synthesis and causes cell death when delivered inside a cell. Development of commercial Saporin results in a technology termed ‘molecular surgery’, with Saporin as the scalpel. Its low toxicity (it has no efficient method of cell entry) and sturdy structure make Saporin a safe and simple molecule for many purposes. The most popular applications use experimental molecules that deliver Saporin via an add-on targeting molecule. These add-ons come in several forms: peptides, protein ligands, antibodies, even DNA fragments that mimic cell-binding ligands. Cells that do not express the targeted cell surface marker will not be affected. This review will highlight some newer efforts and discuss significant and unexpected impacts on science that molecular surgery has yielded over the last almost four decades. There are remarkable changes in fields such as the Neurosciences with models for Alzheimer’s Disease and epilepsy, and game-changing effects in the study of pain and itch. Many other uses are also discussed to record the wide-reaching impact of Saporin in research and drug development.